Victims of Robber- Induced Intoxication - Muaz,HassanAliChoudry;HassanZia (Journal of Rawalpindi Medical College, 2018)
Background: To study the presentation and clinical outcome of victims of robber- induced intoxications. Methods: In this retrospective study the data of robber induced intoxicated patients was taken from Rescue 1122 service. Death registers from both the hospitals were investigated for deaths due to poisoning cases. Self-taken poisoning cases were excluded. Death registers were tallied with death books provided to medical officers in the emergency department. Result: A total of 4624 patients came with intoxication in medical emergency of both the tertiary care hospitals of the district. 71 patients died in the total mentioned time period. The casualties were maximum in 2013 (19). All the patients were male. No gastric, urine, or blood toxicology reporting was done for any of the patients. All the patients were treated symptomatically. No postmortem was done after any deaths.. Conclusion: The unavailability of toxicology reporting is a hurdle in giving a proper care.